PRAKTIK MANAJEMEN SDM BERKELANJUTAN (S-HRM) DALAM PEMBENTUKAN PERILAKU KARYAWAN - Pardede, Cicilia Chandra; Paleni, Herman (Jurnal Media Ekonomi (JURMEK), 2025)
Employee behavior is an important determinant of organizational effectiveness and productivity. This study aims to examine how sustainable human resource management (S-HRM) practices shape employee behavior at PT Nusantara Gemilang Mandiri in Lubuklinggau City. This study uses a qualitative approach through in-depth interviews with employees and managers to explore their experiences with the implementation of S-HRM; the data is analyzed thematically to identify patterns of practice and their impact on work behavior. The results show that systematic attention to welfare, occupational safety and health, competency development, and employee engagement increases job satisfaction and motivation; this increase correlates with higher productivity, the emergence of innovative initiatives, and more proactive and responsible work behavior. The findings confirm that S-HRM not only supports organizational sustainability, but also directly shapes positive employee behavior at gas station operations. Practically, this research provides direction for similar companies to prioritize welfare programs, safe working environments, and sustainable development as levers for superior work behavior; academically, this study adds to the evidence on the effects of S-HRM on employee behavior in the retail fuel sector. The limitations of this study open up opportunities to use a larger sample size in the future